RONC-01. A 10 year, single institution experience of re-irradiation for paediatric intracranial tumours. (3rd June 2022) - Durno, Kimberley; Lim, Pei; Gandhi, Vanita; Shankar, Ananth; Dahl, Christine; Jorgensen, Mette; Gaze, Mark; Gains, Jenny; Chang, Yen-Ch'ing
Abstract: INTRODUCTION: Re-irradiation has become integral in the management of relapsed and recurrent intracranial tumours in children. It is used as salvage therapy for a number of tumours including; diffuse intrinsic pontine glioma (DIPG), high grade glioma (HGG), ependymoma and medulloblastoma. We report the patient demographics, dose, outcomes and toxicity for patients treated with re-irradiation at our institute. METHODS: 33 patients with a diagnosis of DIPG (n=11, 33%), ependymoma (n=11, 33%), HGG (n=4, 12%) or medulloblastoma/sPNET (n=7, 21%), treated with intracranial re-irradiation since 2012 were analysed in this retrospective study. Statistical survival analysis was performed. RESULTS: The median follow-up was 19 months (range 0–216 months). The median age at re-irradiation was 10 years (2-20 years). The median time from first radiation to re-radiation was 34 months (range 3–113 months). Re-irradiation techniques included; photons (n=26), protons (n=2) and stereotactic radiotherapy (n=6). The median re-irradiation dose was 36.37Gy EQD2 (range 20-95.05Gy), given in dose per fraction between 1.8Gy–2Gy. The median overall survival (OS) and progression free survival (PFS) for the cohort was 15.68 months and 7 months respectively. For DIPG, the median OS and PFS were 6.12 months and 4 months respectively. At 2 years, the OS and PFS rates for the cohort were 34.37% and 32.45% respectively. For the non-DIPG cohort, the 2 year OS and PFS rates were 55.37% and 48.13% respectively. In the DIPG cohort, 88% (n=7) had a reported symptomatic benefit from re-irradiation. A stable or improved radiological response was reported in majority of patients (78%, n=18). No acute or late toxicities ≥ grade 3 were reported within the cohort, specifically, there were no reports of brainstem necrosis. CONCLUSION: Re-irradiation for paediatric intracranial tumours is safe and offers a benefit to patients. Further work is ongoing to evaluate cumulative brainstem doses and predictive variables.